The Circular Economy in Iraq : Obstacles of Transition and Opportunities for Achieving Sustainable Development - Nadia Mahdi Abdel Qader (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study diagnoses obstacles to transitioning to a circular economy in Iraq and analyzes opportunities for sustainable economic development. It employs a comprehensive descriptive analysis of economic, social, and environmental data related to the circular economy in Iraq. The findings reveal a decline in per capita economic growth in Iraq, dropping from 10.8% in 2016 to 4.3% in 2022, with some years experiencing negative growth. This decline stems from the economy's heavy reliance on the oil sector, which accounts for 61.1% of GDP, and insufficient infrastructure for clean production models and resource recycling. The study recommends effective government strategies to diversify away from oil dependence by developing sustainable agriculture, green industries, and eco-tourism. It stresses the need to invest in waste recycling and renewable energy projects and to offer tax incentives for small and medium-sized enterprises (SMEs). Additionally, it concludes that collaboration with developed countries and international organizations could accelerate Iraq's transition to a circular economy, enhancing economic sustainability and improving living standards.